Lipid droplets associated perilipins protein insights into finding a therapeutic target approach to cure non-alcoholic fatty liver disease (NAFLD) - Aman Sharma (SpringerOpen, 2022)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is now the most common form of chronic liver disease in the world, and it's linked to a slew of other risk factors including diabetes, obesity, dysbiosis and inflammatory bowel disease. More than 30 years ago, a patient was diagnosed with fatty liver with excessive fat accumulation in hepatocytes, a disorder known as hepatosteatosis. There will be no promising therapeutic medicines available from 1980 to 2021 which can reverse the fatty liver to normal liver state. In this review, we highlighted on lipid droplet associated protein which play a major role in accumulation of fat in liver cells and how these cellular pathway could be a promising therapeutic approach to treat the fatty liver disease. Main body Over the last few decades, Western countries follow a high-fat diet and change their lifestyle pattern due to certain metabolic disorders prevalence rate is very high all over the world. NAFLD is a major health issue and burden globally nowadays. Researchers are trying to find out the potential therapeutic target to combat the disease. The exact pathophysiology of the disease is still unclear. In the present decades. There is no Food and Drug Administration approved drugs are available to reverse the chronic condition of the disease. Based on literature survey, lipid droplets and their associated protein like perilipins play an eminent role in body fat regulation. In this review, we explain all types of perilipins such as perilipin1-5 (PLIN1-5) and their role in the pathogenesis of fatty liver which will be helpful to find the novel pharmacological target to treat the fatty liver. Conclusion In this review, majorly focussed on how fat is get deposited into hepatocytes follow the cellular signalling involved during lipid droplet biogenesis and leads to NAFLD. However, up to date still there mechanism of action is unclear. In this review, we hypothesized that lipid droplets associated proteins like perilipins could be better pharmacological target to reverse the chronic stage of fatty liver disease and how these lipid droplets associated proteins hide a clue to maintain the normal lipid homeostasis in the human body.